Hubungan Pola Asuh, Pendidikan, Sikap Orang Tua Dengan Perkembangan Kreativitas Pada Anak Usia Prasekolah Di PAUD Sartika Kabupaten Sumenep Tahun 2020: The Relationship between Parenting Style, Education, Parental Attitudes and the Development of Creativity in Preschool Age Children at PAUD Sartika, Sumenep Regency, 2020 - Damayanti, Cory Nelia; Puspitasari, Dian Ika (Jurnal Abdi Keperawatan dan Kedokteran, 2023)
Growth and development in the preschool period is a very influential basic stage and forms the basis for further development. Parents play the main and first role for children's education, caring for, raising and educating children. The purpose of this study was to determine the relationship between upbringing, education, parental attitudes and the development of creativity in preschool children at PAUD Sartika, Sumenep Regency in 2020. This research is a research with descriptive analytic method with cross sectional design. The population in this study were all parents and preschool-age children who were at PAUD Sartika in 2020 with a total population of 30 people. The sampling technique used by researchers is total sampling. The instrument used in this study was a questionnaire sheet. Data analysis techniques used univariate analysis, bivariate analysis and chi-square test. The results showed that there was a relationship between parenting style and the development of creativity in preschool children with a p value = 0.001 (p <0.05), there was no relationship between education and the development of creativity in preschool children with a p value = 0.578 (p <0.05) and there was the relationship between parental attitudes and the development of creativity in preschool children with p value = 0.01 (p <0.05).